Host specificity and aggregation for a widespread mistletoe in Campo Rupestre vegetation - Guerra, Tadeu J.; Pizo, Marco A.; Silva, Wesley R. (Flora. Morphologie, Geobotanik, Oekophysiologie, 2018)
•Psittacanthus robustus is an widespread parasitic plant in campo rupestre vegetation.•Distribution pattern was highly aggregated at host tree and vegetation scales.•Usually infects the taller trees, preferentially Qualea cordata.•Mistletoe presented host specificity within Myrtales clade, specially Vochysiaceae. Assessment of host infection and distribution patterns are crucial to understand the underling mechanisms that shape parasitic plant spread in natural ecosystems. However, such data remain scarce for mistletoes inhabiting Brazilian campo rupestre vegetation, old-growth montane fire-prone grasslands. We evaluated the host range and distribution patterns of the mistletoe Psittacanthus robustus (Loranthaceae) at seven 1-ha plots located at in Serra do Cipó, southeastern Brazil. We investigate if the frequency of parasitism by P. robustus is directly related to the relative abundance of host tree species in the community, and how prevalence and intensity of infection vary among different host tree species. Average mistletoe density was 120 individuals ha−1, which parasitized eight host species, including trees and shrubs in five families. Four tree species, Vochysia thyrsoidea, Qualea cordata (Vochysiaceae), Trembleya laniflora and Miconia ferruginata (Melastomataceae), comprised 95% of infected individuals. Twenty two percent of 1,108 trees sampled were parasitized by P. robustus, with host specificity within species in Myrtales Clade. Prevalence increased with host height for all tree species, with a highly aggregated distribution in few taller host trees within rocky outcrop patches in campo rupestre. The unveiling patterns of host infection and mistletoe distribution, support future studies addressing plant-plant, bird-plant and fire-plant interactions that might shape infection dynamics of this widespread mistletoe species in campo rupestre.